A Theoretical Framework for Triguna-Based Psychospiritual Rehabilitation: The Srimad Bhagavad Gita-Inspired Intervention Module for Offenders - Kumkaria, Bodhraj; Tiwari, Himalaya (International Journal of Psychosocial Rehabilitation, 2019)
This theoretical review proposes a Bhagavad Gita-inspired psychospiritual rehabilitation framework for correctional settings, rooted in the Triguna model of Indian psychology. Drawing from verses of the Srimad Bhagavad Gita, the intervention aims to reduce Rajas (restlessness, impulsivity) and Tamas (inertia, apathy) while enhancing Sattva (clarity, compassion, and self-awareness) among offenders. The eight-week module integrates chanting, guided contemplation, Gitabased affirmations, journaling, and group reflection to foster inner transformation. Weekly themes address self-concept healing, emotional regulation, trauma reframing, and moral agency. Though inspired by a Hindu scripture, the intervention is presented through a nonsectarian psychospiritual lens, emphasizing universal principles of inner change and ethical growth. This paper outlines the theoretical rationale, psychospiritual mechanisms, and thematic structure of the module. The review further discusses how this culturally grounded framework contributes to rehabilitation science by integrating indigenous knowledge systems with contemporary psychological constructs.